AGRESIVITAS ANAK KORBAN EKSPLOITASI DI KAWASAN LAMPU MERAH TABEK GADANG PEKANBARU RIAU - Afiany Firdausa Br Purba; Tri Umari; Rosmawati Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the aggressive behavior experienced by child victims of exploitation and the factors that encourage exploited children to behave aggressively in the red light area of Tabek Gadang, Pekanbaru, Riau. Child victims of exploitation tend to get various forms of violence against themselves, thus allowing child victims of exploitation to commit acts of violence. This type of research uses descriptive research qualitative. The research subjects in this study were 3 people who were taken using accidental (insindental) techniques. The instruments used in this study were observation and interviews. Based on the results of this study, child victims of exploitation commit and experience aggressive physical and verbal behavior. The results of this study indicate that child victims of exploitation engage in aggressive behavior in the form of shouting, coercing, insulting and kicking, while the aggressive behavior experienced is being yelled at, insulted, yelled at, insulted, forced, kicked, pushed, and hit in the legs, factors that encourage child victims of exploitation. perform aggressive behavior, namely peers and the environment.Key Words: Aggressiveness, Child Victims of Exploitation, Descriptive Researc Qualitative